Assessing the activity of mud volcanism using boron isotope ratios in pore water from surface sediments of mud volcanoes off Tanegashima (SW Japan) - Mitsutome, Yuki; Agena, Ko; Toki, Tomohiro; Song, Ke-Han; Shinjo, Ryuichi; Ijiri, Akira (Frontiers in Marine Science, 2023)
Mud volcanoes can cause various geohazards, so it is very important to know their activity level and their distribution. Surface sediments were collected from four submarine mud volcanoes (MVs) off Tanegashima (SW Japan), namely, MV1, MV2, MV3, and MV14. We extracted pore water from the surface sediments and investigated its chemical and isotopic compositions. The sodium (Na) and chloride (Cl-) concentrations decreased and the boron (B) and lithium (Li) concentrations increased with increasing depth, suggesting that some fluids with lower Na and Cl- concentrations and higher B and Li concentrations than seawater were supplied upward from the deep sub-seafloor. The fluid advection velocities estimated from the pore-water profiles differed for each MV, and those of MV3 were the fastest (14 cm/yr) in this study. The estimated equilibrium temperature with clay minerals using Na and Li concentrations were 93-134°C, corresponding to the temperature of environments around 3.7 to 5.3 km below the seafloor. This indicates that these components originated from these depths and that the origin depth did not reach the plate boundary in this area. The B isotope ratio in the pore water was extremely high up to +57 ‰, suggesting that it was strongly affected by adsorption onto the surface of the sediments. A higher B isotope ratio (+57 ‰) was detected in MV3, which was considered to be more active, indicating that more B was adsorbed onto clay minerals supplied from deeper depths.